Blockchain-Driven Optimized Chaotic Encryption Scheme for Medical Image Transmission in IoT-Edge Environment - Goli Archana; Rajeev Goyal; K. M. V. Madan Kumar (International Journal of Computational Intelligence Systems)
Abstract Internet of Things (IoT) is adopted in a wide spectrum of applications in which a vast amount of data are produced and distributed to centralized cloud platforms to deliver various services. It involves smart devices that collect thousands of terabytes of heterogeneous data and deployed this to make instant decision that aids for the better performance and most comfort life. Traditional IoT architecture is heavily centralized, where it stores the most sensitive information that creates the multiple threats and security breaches as the attackers target towards these centralized cloud systems. To improve the security chain in IoT environment, edge computing (EC) was introduced to distribute the applications of IoT at the edge of the communication networks. However, these edge-based IoT are also vulnerable to many threats due to their decentralized and in secured management. Block chain (BC) technology offers a most trusted solution to resolve the security issues in the IoT-Edge computing environment. This research study presents the block chain driven medical image encryption technique using modified honey badger optimization with the ensemble chaotic systems. The proposed block chain framework uses the divergent methods that integrates differential scroll, Hénon chaotic maps and modified honey badger optimization to generate the optimum keys and high secured image data. These high secured data are stored in the block chain, ensuring the image security to be stored in edge nodes. The complete framework was experimented using Ethereum using Ganache API and Python3.19 are utilized as the major programs for designing the varied interfaces of the recommended model. The comprehensive experimentation is undertaken to assess the security strength of the recommended encryption scheme. The evaluation metrics like as NACI, UACI, Entropy and standard verification methods such as NIST standard tests are deployed and analyzed. To prove it security strength, proposed secured BC framework is compared with the wide-variety of secured frameworks. The experimental findings reveal that the suggested framework establishes a more robust and secure environment for image exchange, surpassing the performance of other blockchain-based systems in terms of integrity, robustness and security. Finally, the paper spreads the bright light of advantages in deploying the proposed framework to formulate the most secured environment in the IoT-Edge environment for medical image transmission.